Development of Concept Change-Oriented Acid-Base Worksheet to Eliminate Acid-Base Misconceptions in Senior High School Students - Amry, Urwatil Wutsqo (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2025)
Facts in the field showed that students encountered misconception towards several basic concepts of acid-base. The misconception occurred is resistant and hard to be changed. To change the misconception occurred, the students must experience cognitive conflict that may lead them to do concept changing. Concept-change oriented learning is effective in preventing students from misconception. By the use of worksheet that oriented to concept-change will help reducing misconception encountered by the students. The aim of this study is to determine the process of developing acid-base worksheet which oriented to concept-change, to know the feasibility of the developed worksheet and to determine the effectiveness of the developed worksheet in reducing misconception that students face. The study used Borg and Gall theory. The result of the study showed that the developed worksheet is feasible to be used with validation value of 90,11%, and the developed worksheet is also effective in eliminating misconception encountered by the students, with pre-test value of 67.6% and post-test value of 2%.